Understanding Entrepreneurial Behaviour of Makhana Growers in Bihar Using SEM-PLS Approach (Indian Journal of Extension Education, 2025)
The study aimed to identify the factors that influence the entrepreneurial behaviour of Makhana growers. During 2022-24, data were collected from 120 Makhana growers across four leading districts (Purnea, Darbhanga, Katihar, and Madhubani) in Bihar using a structured schedule. Various socio-economic and entrepreneurial characteristics of the farmers were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings revealed that more than three-fifths (67.50%) of makhana growers possessed medium entrepreneurial behavior followed by 19.16 per cent of them with low level of entrepreneurial behaviour and only 13.33 per cent of them exhibited high level of entrepreneurial behaviour. The findings indicated that variables Achievement, Production, and Risk were strong indicators of entrepreneurial behaviour. Makhana farmers always dare to take risks and persistent and disciplined to undertake cultivation activities. Additionally, knowledge and skills need to be constantly updated to enhance the ability to innovate and be creative in carrying makhana cultivation activities successfully.